Abnormal neuroimaging in a case of infant botulism - Ryan J Good; Kevin eMessacar; Nicholas V Stence; Craig A Press; Todd C Carpenter (Frontiers Media S.A., 2015)
We present the first case of abnormal neuroimaging in a case of infant botulism. The patient presented with clinical findings of constipation, bulbar weakness and descending, symmetric motor weakness which are consistent with the classic findings of infant botulism. Magnetic resonance imaging (MRI), however, revealed restricted diffusion in the brain and enhancement of the cervical nerve roots. Traditionally, normal neuroimaging was used to help differentiate infant botulism from other causes of weakness in infants. Abnormal neuroimaging is seen in other causes of weakness in an infant including metabolic disorders and hypoxic-ischemic injury but these diagnoses did not fit the clinical findings in this case. The explanation for the MRI abnormalities in the brain and cervical nerve roots is unclear as botulinum toxin acts at presynaptic nerve terminals and does not cross the blood-brain barrier. Possible explanations for the findings include inflammation from the botulinum toxin at the synapse, alterations in sensory signaling and retrograde transport of the botulinum toxin. The patient was treated with human botulism immune globulin and had rapid recovery in weakness. A stool sample from the patient was positive for Type A Clostridium Botulinum toxin eventually confirming the diagnosis of infant botulism. The findings in this case support use of human botulism immune globulin when the clinical findings are consistent with infant botulism despite the presence of MRI abnormalities in the brain and cervical nerve roots.